Study of Interconnectivity of Operations and Its Effects on Capability of Firm: Exploring the Relationship between Operations Capability and Firm Competitiveness (Journal of Advances and Scholarly Researches in Allied Education, 2011)
This  paper examines  the  relationship of  a  firm’s operations  capability  on  the perceived  competitiveness  of  its  customer and efficiency  performance.  Measures of operations  capability  are developed  for  this purpose.  Three  hypotheses that  relate  operations capability  to competitive  turbulence  and firm  competitiveness  are tested  using  data from  a  sample of  Australian  SMEs (n  =152). The  impact of  operations  capability on  firm  competitive perceptions  was  found to  be  significant while  controlling  for firm  type variables:  SME status,  manufacturing  focus and  competitive  turbulence. The  perception  of competitive  turbulence  was not  related to  operations capability  development.  The paper  concludes  considering some  practices  adopted by  SMEs,  which has  been  identified here  as a  strong  predictor of  firm  competitiveness.